Grammatical Competence Across Different Learning Styles - Septiana, Ayu Rizki; Hanafi, Moh (Universitas Pahlawan Tuanku Tambusai, 2024)
Effective grammar instruction should integrate a variety of activities that cater to different learning styles. This research is intended to investigate students’ learning style, to investigate students’ grammatical competence and to find out whether any significant differences on students’ grammatical competence across different learning style. The design of this present research was convergent mix method which intended to analyze the data from quantitative and qualitative separately but complement each other. There were 15 students who became the sample of this research. In addition, in order to take the data, there were two instruments used, namely, grammar test and learning style questionnaire. The result of the questionnaire showed that the major preference of the learning style was visual learning style. Meanwhile, the grammar test showed the mean score of 86 or A- in average. Further, the result of hypothesis testing using One-way Anova on IbM SPSS 26 found that there is no significant difference on students’ grammatical competence among auditory, visual and kinesthetics learning styles.